2021
DOI: 10.2147/amep.s328648
|View full text |Cite
|
Sign up to set email alerts
|

A Survey-Weighted Analytic Hierarchy Process to Quantify Authorship

Abstract: Background: Authorship is a pinnacle activity in academic medicine that often involves collaboration and a mentor-mentee relationship. The International Committee of Medical Journal Editors criteria for authorship (ICMJEc) are intended to prevent abuses of authorship and are used by more than 5500 medical journals. However, the binary ICMJEc have not yet been quantified. Aim: To develop a numeric scoring rubric for the ICMJEc to corroborate the authenticity of authorship claims. Methods: The four ICMJEc were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The criteria were the challenges which the SSDFs have reported during interview sessions and grouped per theme using the TCA. To prioritize these challenges, we employed the approach by Ing (2021), which aggregates the total scores and finds the average of each criterion and sub-criterion (this is according to the main study objective) [132]. As stipulated by Saaty (1987) a consistency ratio below 10% is considered feasible to proceed with the analysis.…”
Section: Ahp Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria were the challenges which the SSDFs have reported during interview sessions and grouped per theme using the TCA. To prioritize these challenges, we employed the approach by Ing (2021), which aggregates the total scores and finds the average of each criterion and sub-criterion (this is according to the main study objective) [132]. As stipulated by Saaty (1987) a consistency ratio below 10% is considered feasible to proceed with the analysis.…”
Section: Ahp Applicationmentioning
confidence: 99%
“…The AHP synthesis yielded the themes according to their contribution to the overall goal. In completing the pairwise comparison matrix this study adopted the approach by Ing (2021), which finds the difference between each criterion and sub-criteria [132] and converts it to an equivalent form in Saaty's intensity scale of importance [81]. The study AHP ranking revealed that HC had the greatest priority of 0.5713 and was ranked first, followed by UWP with 0.1578, D with 0.0786.…”
Section: Sub-themesmentioning
confidence: 99%
“…This study draws on the theoretical framework of nurses' core competence, and adopts various research methods, including literature research, semi-structured interview, Delphi method and hierarchical analysis method, to construct the core competence evaluation index system [18]. The application of hierarchical analysis helps to determine the weight of core competence indicators and improve the scienti city of research results [19]. The effectiveness of the Delphi method mainly depends on the representativeness, enthusiasm and authority of the consulting experts: In this study, 15 experts were selected, who are from 10 provinces and cities, with a certain regional representation.…”
Section: Reliability Of Research Resultsmentioning
confidence: 99%
“…Admittedly, defining ‘substantial’ contribution may be difficult, although a contribution scoring system may be helpful 20. That said, ICMJE explicitly rejects solely data-gathering, funding, general supervision and editing19—activities comprising a large proportion of guest authorship.…”
Section: Definitionsmentioning
confidence: 99%